PELAKSANAAN PENGAWASAN DINAS PERHUBUNGAN TERHADAP TRAFFICH LIGHT DI KOTA PEKANBARU - Naldi, Rizki; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Dinas Perhubumgan Komunikasi Dan Informatika (Dishubkominfo) Pekanbaru City is the one from many institution that serve and set affair about traffic and rood transportation in Pekanbaru City Wheter In Land Area, Sea, Air, And Also Post And Telecommunication. In Area Regulation Pekanbaru City Number 2 Year 2009 About Traffich And Road Transportation In Pekanbaru City that contained in section 191 and section 194 sentence (2) Dinas Perhubungan manage, Keep and look after condition of traffich signal giver. In order to keep the function, as remain to this decision. But problem that happen is the lack of monitoring at field so that a number of traffich light that exist in Pekanbaru City got damage and not operated in a long time. The target of this research is to know how the monitoring excetution to traffich light in Pekanbaru City. To analizhat problem the writer used the Manullang thein that suitable with that problems namely the procces from monitoring. This research is a descriptive research with qualitative method, where the way to get the data is with observation technique and interview with the key information as key sources and snowball sampling in determination after shocus informants. The conclusion that we can take from this research is in Monitoring Implementation Dinas Perhubungan Against Traffich Light At Pekanbaru City is cess effective and unrealized well. Because many of phenomenons that often happen at the field point location prone to damage to traffich light and even. Some that did not function and operate as it should. So it make the flow of traffich can not run normally and make uneasy for riders in road traffich. Therefore now to increase survei ence on employees and provide insight and direction to the implemention of the work tone really well so that goals and objective can be accomplished. With that is expected.Key Word : Implementation, Monitorng, Traffich Light